'Urf of Cyberspace: Solutions to the Problems of Islamic Law in the Digital Age - Ita Musarrofa; Holilur Rohman (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Human interaction with information and communication technologies has created a new culture in the digital age. It impacts new legal issues that demand solutions based on Islamic law. A theory incorporating culture in law construction is termed ‘urf’ in uṣūl al-fiqh. The purpose of this article is to investigate the role of ‘urf in the establishment of law for cyberspace problems. As a data source, this article employs a virtual ethnographic method with cyberculture products. The application of ‘urf in adapting culture in cyberspace is studied using Jasser Auda’s maqāṣid al-sharī'ah theory. This study discovered that culture in cyberspace is generated by netizens’ externalization, objectivation, and internalization processes. The ‘urf that applies in cyberspace is included in the ‘urf khaṣṣ. Meanwhile, the stated legislation must allude to the realization of human advantage, which means that the six aspects of Jasser Auda’s system must be considered when negotiating between revelation, fiqh, and ‘urf in cyberspace. Thus, the ‘urf of cyberspace can be employed as a legal element in digital-era situations.